Guidelines for reporting of statistics for clinical research in urology. (20th January 2019) - Assel, Melissa; Sjoberg, Daniel; Elders, Andrew; Wang, Xuemei; Huo, Dezheng; Botchway, Albert; Delfino, Kristin; Fan, Yunhua; Zhao, Zhiguo; Koyama, Tatsuki; Hollenbeck, Brent; Qin, Rui; et al.
Abstract : In an effort to improve the quality of statistics in the clinical urology literature, statisticians at European Urology, The Journal of Urology, Urology and BJU International came together to develop a set of guidelines to address common errors of statistical analysis, reporting, and interpretation. Authors should 'break any of the guidelines if it makes scientific sense to do so', but would need to provide a clear justification. Adoption of the guidelines will in our view not only increase the quality of published papers in our journals but improve statistical knowledge in our field in general.